Comparison the PH of roots after intra canal placement of four types of calcium hydroxide (An in vitro study) (Mustansiria Dental Journal, 2018)
The successful outcome of endodontic treatment depends on the reduction orelimination of bacteria present in an endodontic infection. It has been reported thatchemo-mechanical instrumentation alone is not enough for this purpose.The purpose of this in vitro study was to compare the pH changes that occurredover a period of 14 days using four types of calcium hydroxide. Four types of calciumhydroxide materials were filled in fifty extracted single rooted teeth which were keptin individual vials containing distilled water at a pH of (7.4). Digital pH-meter wasused to measure the pH of different groups at two hours, 24 hours, 7 days & 14 daysafter immersion of the specimens. The mean pH was found for all groups andstatistical analysis was carried out using ANOVA and POST HOC TEST (LSD).Calcium hydroxide was found to significantly raise the root PH. Therefore calciumhydroxide is an effective choice in clinical practice to be used as intra canalmedicament between appointments.